2021
DOI: 10.1093/femspd/ftab020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic gene expression in salivary glands of the cat flea during Rickettsia felis infection

Abstract: The cat flea, Ctenocephalides felis, is an arthropod vector capable of transmitting several human pathogens including Rickettsia species. Earlier studies identified Rickettsia felis in the salivary glands of the cat flea and transmission of rickettsiae during arthropod feeding. The saliva of hematophagous insects contains multiple biomolecules with anticlotting, vasodilatory, and immunomodulatory activities. Notably, the exact role of salivary factors in the molecular interaction between flea-borne rickettsiae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…However, a sialotranscriptome of the cat flea revealed several flea molecules that may be influenced by rickettsial infection, including AMPs and targets of the Toll or IMD pathways [78]. Furthermore, the synergistic or regulatory activities of flea salivary gland secreted molecules during rickettsial infection and transmission to vertebrate hosts are in the early stages of characterization [79]. With both R. typhi and R. felis detected within salivary glands of infected fleas, further investigation is warranted to determine the impact of flea saliva on transmission.…”
Section: Insect-borne Rickettsiaementioning
confidence: 99%
“…However, a sialotranscriptome of the cat flea revealed several flea molecules that may be influenced by rickettsial infection, including AMPs and targets of the Toll or IMD pathways [78]. Furthermore, the synergistic or regulatory activities of flea salivary gland secreted molecules during rickettsial infection and transmission to vertebrate hosts are in the early stages of characterization [79]. With both R. typhi and R. felis detected within salivary glands of infected fleas, further investigation is warranted to determine the impact of flea saliva on transmission.…”
Section: Insect-borne Rickettsiaementioning
confidence: 99%
“…The goal of this study was to identify and characterize the proteomic response of the cat flea, C. felis, to feeding of uninfected cat blood and blood from cats experimentally instance, the responses of X. cheopis' digestive tract to infection by Y. pestis (Bland et al, 2020), C. felis' midgut to Rickettsia felis (Dreher-Lesnick et al, 2010), and C. felis' salivary glands to R. typhi (Danchenko et al, 2021) have been previously reported. Herein, we used proteomic approaches to investigate if: i.)…”
Section: Discussionmentioning
confidence: 99%
“…A vaccine targeting both flea fitness and pathogen competence is an attractive choice requiring the identification of flea proteins/metabolites with a dual effect. Even though recent developments in vector and pathogen omics have advanced the understanding of the genetic factors and molecular pathways involved at the tickpathogen interface, leading to discovery of candidate protective antigens (de la Fuente et al, 2007a;de la Fuente et al, 2007b), only a few studies have focused on the interaction between fleas and flea-borne pathogens (Dreher-Lesnick et al, 2010;Brown, 2019;Bland et al, 2020;Danchenko et al, 2021;Laukaitis and Macaluso, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Newly emerged cat fleas were obtained from Elward II (Soquel, CA) and maintained on defibrinated bovine blood (HemoStat Laboratories, Dixon, CA) within an artificial dog feeding unit [23]. Prior to use in bioassays, genomic DNA (gDNA) was extracted from a portion of fleas and confirmed Rickettsia-negative by quantitative real-time PCR (qPCR) [24,25]. In order to generate R. felis-infected donor cat fleas, newly emerged cat fleas were pre-fed HI bovine blood for 24 hrs, starved for 5-6 hrs, then exposed to the R. felis-infected bloodmeal (3 × 10 10 rickettsiae/700 μl) for 24 hrs [8].…”
Section: Fleas Ticks and Mosquitoesmentioning
confidence: 99%
“…Assessment of rickettsial infection by qPCR was performed with a LightCycler 480 Real-Time PCR system (Roche, Indianapolis, IN). The plasmid pCR4-TOPO-RfelB was used as a standard template to create serial 10-fold dilutions and matched with RfelB primers and probe as previously described [24,25]. For An.…”
Section: Sample Preparation and Rickettsial Quantification By Pcrmentioning
confidence: 99%